PENYELESAIAN PERKARA PEMUTUSAN HUBUNGAN KERJA DI PENGADILAN HUBUNGAN INDUSTRIAL KOTA PALEMBANG - Puspasari, Ayu; Meirani, Wasitoh; Erwin, Muhammad; Suroso, Suroso (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
This study aims to explain and analyze the settlement of disputes in cases of termination of employment at the Palembang Industrial Relations Court. The research method used in this research is a type of empirical legal research (juridical empirical) that sees law as facts. The results showed that the incidence of termination of employment in Palembang City was caused by several factors, but the most dominant was that qualified workers/laborers resigned. The process of resolving a case of termination of employment at the Palembang Industrial Relations Court can be carried out using a quick program and an ordinary event. The two events, which are most often used to resolve cases of termination of employment at the Palembang City Industrial Relations Court, are normal. The obstacle related to the judges of the Palembang City Industrial Relations Court in resolving cases of termination of employment is that the parties do not agree on severance pay. The author suggests that the parties in a case state cooperative, not concerned with their respective egos related to severance pay so that the settlement of the case for termination of employment at the Industrial Relations Court can run smoothly. Besides, Industrial Relations Court judges also need to explain if the party does not agree on severance pay.Keywords:  Settlement; Termination of Employment; Industrial Relations Court.